Extraction of Zingiber officinale oil by using soxhlet extraction method - Nur Daniati, Zulkifli (2010)
Ginger is the common name for the Zingiber officinale which is one of the plants that belongs to the Zingiberaceae family.Ginger is a very useful herb plant that is usually indigenous to the Jamaica, India, China, Indonesia, Nigeria and Southeast Asia. It is found that zingiberene is the main compound in the ginger.The ginger oil is widely used in both traditional and contemporary natural medicine and also is commercialized for use in food as well.The objective of this research is to extract ginger oil by using Soxhlet Distillation,to evaluate the effect of different solvent on the extraction and to investigate the effect of extraction time.Four types of solvents are used in this research which is methanol, dichloromethane, benzene and acetone while the extraction time is varied about 4 hours,6 hours,8 hours and 10 hours.After extracting the oil using Soxhlet Distillation, the oil then is separated from the solvent by rotary evaporator and finally the sample was analyzed using GC-MS in order to identify the components in the oil. Methanol gave highest yield of the Zingiber Officinale oil at 8 hours extraction time which is 27.33% of mass yield.